Cloning and Functional Characterization of Roaz, a Zinc Finger Protein that Interacts with O/E-1 to Regulate Gene Expression: Implications for Olfactory Neuronal Development - Tsai, Robert Y. L. (J Neurosci, 1997)
We have identified a protein, Rat O/E-1-associated zinc finger protein (Roaz), that plays a role in regulating the temporal and spatial pattern of olfactory neuronal-specific gene expression. This protein functions by interacting with the olfactory factor O/E-1 and modulating its transcriptional activity. Roaz, isolated via a yeast two-hybrid screen, encoded a protein containing 29 C(2)H(2) zinc fingers of the TFIIIA type. The Roaz mRNA was found in brain, eye, olfactory epithelium, spleen, and heart.In situ hybridization data indicated that Roaz was expressed in the basal layer, consisting of neural precursor cells and immature sensory neurons of the olfactory epithelium, but not in the mature receptor cells. We showed that the Roaz protein bound specifically to O/E-1 by using the yeast two-hybrid system. The two proteins formed a stable complex in coimmunoprecipitation and in vitro binding assays. Introduction of Roaz and O/E-1 into cells containing an olfactory promoter-driven luciferase reporter demonstrated that Roaz abolished O/E-1-mediated transcriptional activation. We propose that the function of Roaz is to modulate negatively the transactivational activity of O/E-1 and to act as a switch protein in the coordination of olfactory sensory neuron differentiation.